HPV vaccination crisis in Japan - Hanley, Sharon J B; Yoshioka, Eiji; Ito, Yoshiya; Kishi, Reiko (The Lancet (British edition), 2015)
According to the Global Advisory Committee on Vaccine Safety, "Allegations of harm from vaccination based on weak evidence can lead to real harm when, as a result, safe and effective vaccines cease to be used."